The Looming Menace of Drug Resistant Tuberculosis and the Quest for the Elusive Vaccine - Dr. Abhijit Chaudhury (Journal of Clinical and Biomedical Sciences)
The malady which took away the life of the protagonist in John Bunyan’s book of 1680 “The life and death of Mr Badman” was con-sumption and it was described as “The captain of all these men of death”. Tuberculosis (TB), which was a major killer in the mediaeval times, still remains a formidable disease to reckon with, causing substantial mortality in the economically less developed countries in the world.